Disorders of sex development - Jarząbek-Bielecka, Grażyna; Sowińska-Przepiera, Elżbieta; Wilczak, Maciej (Menopause Review/Przegląd Menopauzalny, 2012)
Disorders of sex development are one of the most important diagnostic and therapeutic problems not only in gynecology and sexology. The birth of an infant with atypically appearing (formerly known as “ambiguous”) genitalia is accompanied by an enormous amount of parental anxiety, concern, and questioning. The importance of a carefully coordinated, thoughtful, sensitive, deliberate and confident approach on the part of the healthcare team cannot be overemphasized. The swift mobilization of pertinent subspecialists, support personnel, and laboratory and radiological diagnostic procedures is crucial for diagnosis, treatment, and management of the infant, including, when appropriate, correct sex assignment as early as possible. Individualized care that addresses medical, psychological, and social needs, while at the same time maintains awareness of the patient’s advocacy, is the goal of the specialized treatment team.